Immune system defects in DiGeorge syndrome and association with clinical course. (9th September 2019) - Nain, Ercan; Kiykim, Ayca; Ogulur, Ismail; Kasap, Nurhan; Karakoc‐Aydiner, Elif; Ozen, Ahmet; Baris, Safa
Abstract: We evaluated 18 DiGeorge syndrome (DGS) patients and aimed to investigate the immunological changes in this population. DGS patients with low naive CD4 + T and CD8 + T cells were defined as high‐risk (HR) patients, whereas patients with normal numbers of naive CD4 + and CD8 + T cells were defined as standard risk (SR) patients. Level of serum IgM, CD3 + T cell counts and percentages of class‐switched memory B cells were significantly low in HR group compared to SR ones. Severe infections and persistent hypoparathyroidism were detected significantly higher in HR group. Patients with reduced percentages of class‐switched B cells had earlier onset of infection, lower blood IgM, lower CD4 + and CD8 + T counts than patients with normal class‐switched memory B cells. Decreased levels of IgM were associated with low numbers of naive CD4 + and recent thymic emigrants T cells. Monitoring the immune changes of patients with DGS would be useful to predict the severe phenotype of disease.